Поетичний діалог Наталі Лівицької-Холодної та Євгена Маланюка - Сподинюк, А. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is dedicated to the revelation of an intertextual dialogic bonds between poems of Natalia Livytska-Cholodna and Yevgen Malaniuk based on autobiographical facts, sensual and erotical perception of the autors’ texts. The features of the meaning of early creative work of Natalia Livytska-Cholodna (on the material of her collection «Fire and asher») are being elucidated. Poetical polemics based on intertextual, psychological, and biographical analysis of the texts of the mentioned authors is being characterized.